Alcohol intake reduction for controlling hypertension - Domínguez‐Cantero, Marcelo (Cochrane Database Syst Rev, 2012)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of interventions to reduce alcohol intake for controlling hypertension in hypertensive people.